Antibacterial effects of Pluchea indica Less leaf extract on E. faecalis and Fusobacterium nucleatum (in vitro) - Agni Febrina Pargaputri; Elly Munadziroh; Retno Indrawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Enterococcus. faecalis (E. faecalis) and Fusobacterium nucleatum (F. nucleatum) are the most common bacteria found in infected tooth root canal. Most of these bacteria often cause failure in endodontic treatments. Pluchea indica Less leaf is a species of plants that has several chemical properties. It consists of flavonoids, tannins, polyphenols, and essensial oils which have been reported as antibacterial agents. Because of its benefits, the extract of Pluchea indica Less leaves may be potentially developed as one of root canal sterilization dressing. Purpose: This study aimed to determine antibacterial activity of Pluchea indica Less leaves extract against E. faecalis and F. nucleatum bacteria. Method: Dilution method was conducted first to show Minimum Inhibitory Concentration (MIC) of the extract against E. faecalis and F. nucleatum. The antibacterial activity test on Pluchea indica Less leaves extract was performed on E. faecalis and F. nucleatum bacteria using agar diffusion method. The Pluchea indica Less leaves extract used for antibacterial activity test was at a concentrations of 100%, 50%, 25%, 12.5%, and 6.25%. Thirty-five petridiscs were used and divided into five groups based on the extract concentration. Result: The results showed strong and moderate antibacterial effects of the Pluchea indica Less leaves extract on E. faecalis at the concentrations of 100% and 50%, while on F. nucleatum only at the concentration of 100% with moderate effect. Conclusion: Pluchea indica Less leaves extract has antibacterial activity against E. faecalis and F. nucleatum bacteria with strong-moderate effect.